Implementation of the extended Kalman filter for determining the optical and geometrical properties of turbid layered media by time-resolved single distance measurements - Baez, Guido Rodrigo (2019)
In this article we propose an implementation of the extended Kalman filter (EKF) for the retrieval of optical and geometrical properties in two-layered turbid media assuming a dynamic setting, where absorption of each layer was changed in different steps. Prior works implemented the EKF in frequency-domain with several pairs of light sources and detectors and for static parameters estimation problems. Here we explore the use of the EKF in single distance, time-domain measurements, together with a corresponding forward model. Results show good agreement between retrieved and nominal values, with rather narrow analytical credibility intervals, indicating that the recovery process has low uncertainty, especially for the absorption coefficients.